2017
DOI: 10.3390/nu9030201
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in Soy Might Have a Higher Role in Cancer Prevention than Previously Expected: Soybean Protein Fractions Are More Effective MMP-9 Inhibitors Than Non-Protein Fractions, Even in Cooked Seeds

Abstract: The search for anticancer MMP-9 inhibitors (MMPIs) in food products has become a major goal for research. MMPIs in soy have been related only to saponins and isoflavones, but recently, low specific protein fractions in soybeans were shown to reduce MMP-9 activity as well. The present work aimed at comparing the MMPI potential of protein fractions (P) and non-protein fractions (NP) isolated from soybean seeds, before and after soaking and cooking, mimicking dietary exposures. Reverse and substrate zymography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…These results agree with those obtained in a recent study [ 46 ], which showed inhibition of this enzyme by Limonium tetragonum extract and are also in line with those reported by other authors [ 47 ] based on the inhibition of MMP-9 with phenolic compounds and proteins from cooked soybean.…”
Section: Resultssupporting
confidence: 93%
“…These results agree with those obtained in a recent study [ 46 ], which showed inhibition of this enzyme by Limonium tetragonum extract and are also in line with those reported by other authors [ 47 ] based on the inhibition of MMP-9 with phenolic compounds and proteins from cooked soybean.…”
Section: Resultssupporting
confidence: 93%
“…Another common protein source consists of the high intake of soybean products such as tofu. A large body of literature demonstrated anticancer effects of soy and its components: proteins, isoflavones and saponins in in vitro and epidemiological studies [ 82 85 ]. In conclusion, similar for the studies in western populations, in which the quality of diet is linked to a lower mortality for chronic diseases including cancer, adherence to Japanese diet is associated to similar outcomes [ 76 ].…”
Section: Dietary Patterns That Affect Immune Function: Mediterranean mentioning
confidence: 99%
“…Soybean seeds in the EU are mainly used as animal feed; however, soybeans also offer high quality and affordable protein for human consumption. The most common soy‐based food product is tofu (soybean curd), a traditional Asian soy food providing an important source of protein for human consumption with additional health benefits (Lima, Oliveira, Saúde, Mota, & Ferreira, ). As the awareness of the consumer for a sustainable production of food products increases, the use of soybean as direct protein source for human diet, instead of indirectly through feeding animals, becomes a logical consequence.…”
Section: Introductionmentioning
confidence: 99%